2022
DOI: 10.1200/op.21.00686
|View full text |Cite
|
Sign up to set email alerts
|

Managing Metastatic Melanoma in 2022: A Clinical Review

Abstract: Cutaneous melanoma remains the most lethal of the primary cutaneous neoplasms, and although the incidence of primary melanoma continues to rise, the mortality from metastatic disease remains unchanged, in part through advances in treatment. Major developments in immunomodulatory and targeted therapies have provided robust improvements in response and survival trends that have transformed the clinical management of patients with metastatic melanoma. Additional advances in immunologic and cancer cell biology hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 181 publications
(254 reference statements)
0
101
0
3
Order By: Relevance
“…On the other hand, we believe that this work focuses on the diagnosis of intrathoracic MM and offers useful practical clues in real life in particular regarding the diagnostic approach, and that it gives also prognostic information, following those already presented in the literature. Indeed, MM has a poor prognosis and, although nowadays there are growing pieces of evidence of efficacious treatment against this pathology [ 33 , 34 ], there is still a need to better understand the underlying mechanisms of the development of lung and other intrathoracic metastasis [ 35 , 36 ], in order to better intercept the predisposed patients and to quickly diagnose them with the proper technique.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we believe that this work focuses on the diagnosis of intrathoracic MM and offers useful practical clues in real life in particular regarding the diagnostic approach, and that it gives also prognostic information, following those already presented in the literature. Indeed, MM has a poor prognosis and, although nowadays there are growing pieces of evidence of efficacious treatment against this pathology [ 33 , 34 ], there is still a need to better understand the underlying mechanisms of the development of lung and other intrathoracic metastasis [ 35 , 36 ], in order to better intercept the predisposed patients and to quickly diagnose them with the proper technique.…”
Section: Discussionmentioning
confidence: 99%
“…There are many treatment options for skin cancers. Surgical excision is the mainstay of local treatment, whereas radiotherapy (RT) is recommended for patients with medically inoperable, surgically unresectable disease or with high predisposition to metastasis [ 117 , 118 ]. Outcomes are generally inferior with RT without surgical resection and tumors may recur quickly after the treatment [ 119 , 120 ].…”
Section: Ddpcr-based Liquid Biopsies For Skin Cancer Monitoring and P...mentioning
confidence: 99%
“…Outcomes are generally inferior with RT without surgical resection and tumors may recur quickly after the treatment [ 119 , 120 ]. Novel systemic approaches, such as targeted therapies and immunotherapies, have revolutionized skin cancer therapy and improved clinical care, especially in the metastatic setting [ 118 , 121 ]. Hedgehog pathway inhibitors (HHi), vismodegib and sonidegib, are relevant examples in this context.…”
Section: Ddpcr-based Liquid Biopsies For Skin Cancer Monitoring and P...mentioning
confidence: 99%
“…However, pilot studies have shown that ADs can be managed without discontinuing ICI treatment [ 9 ]. As ICIs have become a cornerstone of treating metastatic melanoma, it is important to know whether patients with ADs can safely receive this immunotherapy [ 10 ].…”
Section: Pre-existing Autoimmune Skin Diseases In Ici Cancer Patientsmentioning
confidence: 99%